2003
DOI: 10.1212/01.wnl.0000068017.75780.44
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cord dysfunction during neck flexion in Hirayama’s disease

Abstract: Neck flexion may play a role in the pathogenesis of Hirayama disease. Upper limb somatosensory evoked potentials were recorded in five patients with Hirayama disease, six patients with ALS, and 14 healthy subjects. Neck flexion caused a significant amplitude decrease of the N13 cervical response only in patients with Hirayama disease. Direct cord compression or microvascular changes can in theory account for this position-related dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 10 publications
2
31
0
1
Order By: Relevance
“…7 9 Significant amplitude reduction of N13 cervical somatosensory evoked potential (SEP) on neck flexion has been attributed to cord compression or microvascular changes during neck flexion. 10 Spinal MRI in cervical flexion showed forward displacement of dural sac and compressive flattening of lower cervical cord. Cinematographic magnetic resonance imaging (MRI) showed signal void in posterior epidural space pulsating synchronously with cardiac beat suggesting passive dilatation of epidural venous plexus.…”
mentioning
confidence: 97%
“…7 9 Significant amplitude reduction of N13 cervical somatosensory evoked potential (SEP) on neck flexion has been attributed to cord compression or microvascular changes during neck flexion. 10 Spinal MRI in cervical flexion showed forward displacement of dural sac and compressive flattening of lower cervical cord. Cinematographic magnetic resonance imaging (MRI) showed signal void in posterior epidural space pulsating synchronously with cardiac beat suggesting passive dilatation of epidural venous plexus.…”
mentioning
confidence: 97%
“…As postulated in BMMA, in DBMA also probably the short cervical dural canal is unable to compensate for the flexion related increased length of the vertebral canal (18). However, it is difficult to understand how the mechanical compression of an elliptical spinal cord could induce damage to unilateral or bilateral anterior horn cells, and yet remain in the restricted form for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Forward migration of the posterior surface of the dura mater with compression of the spinal cord on MRI obtained with flexion of the cervical spine is characteristic 2,3 . Although neck flexion has been implicated in the physiopathology of JADUE (the disorder was termed "flexion myelopathy" by Kikuchi 5 , the underlying mechanism is still controversial 1,5,8,9 . Some authors consider that JADUE is not a flexion-induced cervical myelopathy, but an intrinsic motor neuron disease.…”
Section: Discussionmentioning
confidence: 99%
“…Since neck flexion has been thought to be the cause of the spinal cord damage, cervical orthosis, spinal fusion by an anterior or posterior approach and duraplasty in com- bination with posterior spinal fusion have been proposed as treatment of JADUE 7 . However, the imaging findings observed in dynamic studies have shown, not only the absence of hypermobility in the cervical spine, but also the increase in the rigidity of the dura as a cause of spinal cord compression 2,3,5,7,9 . Histopathological findings have also suggested that alterations in the laxity of the dural tissue are the basic cause leading to a repeated spinal cord compression and, thus, to spinal cord damage 7 .…”
Section: Introductionmentioning
confidence: 99%